Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen pada Layanan Driver Grab di Kota Bogor - Muhammad Rois Fahmi; Firmansyah, Firmansyah; Muhammad Ikbal Fadillah; Siti Nur Asifa; Vasya Azzahwa; Salsa Septia Putri (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of service quality and price on consumer satisfaction in Grab online transportation services in Bogor City. The study uses a quantitative approach with a survey method, involving 63 respondents who are active Grab users. Data were obtained through a structured questionnaire and have been tested for validity and reliability. The data analysis process was carried out using multiple linear regression to identify the simultaneous and partial effects between independent variables, namely service quality and price, on the dependent variable, namely consumer satisfaction. Prior to analysis, classical assumption tests were conducted including multicollinearity, heteroscedasticity, and normality tests to ensure the accuracy of the regression model. The results of the study indicate that service quality and price significantly affect consumer satisfaction both simultaneously and partially. This emphasizes the importance of improving service quality and determining competitive prices to maintain consumer loyalty. This study provides insights for Grab management and other online transportation sectors to optimize consumer experience-based marketing strategies. By focusing on consumer needs and improving operational aspects, companies can increase their competitiveness in an increasingly competitive market.